Fatigue thresholds as a marker for transition from aerobic-to--anaerobic exercise intensity in intermittent sport players:an electrophysiological study - Saif, Ashi; Khan, Zainab; Parveen, Adila (Akademia Wychowania Fizycznego w Poznaniu)
Introduction. In recent years, there have been contradictions regarding the fatigue thresholds denoting the boundary between heavy and severe exercise domain as the marker for transition from aerobic-to-anaerobic exercise intensity. Aim of Study. This study aims to examine the various fatigue thresholds (critical power, respiratory compensation point and neuromuscular fatigue threshold) as marker for transition from aerobic-to- -anaerobic exercise intensity in intermittent sport players based on the VO2 kinetics, muscle activations and mathematically derived models. Material and Methods. Thirteen male intermittent sport players (age = 21.30 ± 2.52 years; height = 164.76 ± 6.2 cm; weight = 57.03 ± 4.93 kg; BMI = 21.01 ± 1.41 kg/m2) were recruited for this study. The participants performed total 11 sessions, one incremental test for evaluating electromyographic fatigue threshold (EMGFT), four time-to-exhaustion trials for evaluating critical power with mathematical models (CP) and two verification trials, four constant load tests for evaluating critical power based on VO2 kinetics (CP’) and respiratory compensation point (RCP). Results. The Bland–Altman analysis revealed that CP was not in agreement with CP’ (r2 = 0.89, p < 0.00; t = 9.70, Cohen’s f = 0.99). Also, VO2 corresponding to the work rates of CP was significantly different from the CP’ and RCP (p < 0.001). However, work rates corresponding to the CP’ were not significantly different and in agreement to the work rates corresponding to RCP (t = –1.65, p = 0.062; r2 = 0.61, p = 0.66, t = –4.18, Cohen’s f = 1.26) and EMGFT (t = –0.633, p = 0.269; r2 = 0.43, p = 0.342, t = –4.18, Cohen’s f = 0.99), respectively. Conclusions. The CP’, EMGFT and RCP corresponds to similar work rates and can depict the boundary between heavy to severe exercise domains which could be used for performance testing and training the intermittent sport players.
Keywords: VO2max; exercise domains; critical power; respiratory; compensation point; EMG fatigue threshold